CHARACTER BUILDING AGEN PASTORAL:MENUJU PELAYAN PASTORAL YANG KOMPETITIF - Vinsensius Nase (STIPAS St. Sirilus Ruteng, 2016)
The nation live and social civilized must be built from inside. It means the quality of heart and mental of human are the most important thing. So, the charater person is necesarried. It can help in building the character of nation. The pastoral agent should have some qualities, originaland positive character in order totake a part ofnation building. In this article, Vinsen Nase explains about character building ofpastoral agent. Character building is to buid the character of pastoral agent and it is so important for them. Pastoral agents are man and woman that work in serving the religious community and Cahatholic Church. Characater building go hand in hand with mental revolution. What kind of character that belongs to pastoral agent? In case of pastoral agent, the required character comprises of physic, intelectual, emtional and social maturity. All those characters are required in serving the society. Character building could be built through organization, education, family and media.